Providing a home away from home : the Winnebago Indian Boarding School - Johnson, Rachael Renee (My University, 2008)
This paper discusses how the experiences of students at the Winnebago Indian Boarding School, located in Neillsville, Wisconsin, compared to other Native American children at Bureau of Indian Affairs boarding schools. Based out of the Ho-Chunk mission founded in Black River Falls, Wisconsin, the boarding school was supported by the Reformed Church of Wisconsin. Benjamin Stucki, the son of Ho-Chunk missionary Jacob Stucki, took on the responsibility of operating the school in 1919. Stucki?s dedication and devotion to the Ho-Chunk children marked an important difference in how his boarding school operated compared to other BIA schools with many of the dangerous circumstances that surrounded BIA schools not found at the Winnebago Indian Boarding school. Mr. Ben?s lifetime goal became to provide his students with an education and an understanding of the Christian faith.
Keywords: Indians of North America--Education--Wisconsin.; Winnebago Indian School (Neillsville, Wis.); Stucki, J. (Jacob), 1857-1930.; Boarding schools--Wisconsin--History.; Ho Chunk Indians--Education.